Papalele: Dangerous Encounter and Transaction in Conflict - Soegijono, Simon Pieter (KOMUNITAS: INTERNATIONAL JOURNAL OF INDONESIAN SOCIETY AND CULTURE, 2015)
The true peace is still being fought in various countries, indeed Indonesia. It relates with the pluralism life as the main constraint recently. So it is important to raise the individual and community awareness to pluralism. Thus, peace becomes important factor for any country with various identity like Indonesia. This Peace is related to some value, as follows: mutual respect and sense of tolerence to face the conflict of religion, ethnicity and race that takes place at this time. At recent, numerous attempts have done by government, education institution, non-governmental organization, and others independent stakeholder. The strategy of peace recovery can be done by formal activities, like: workshop, training, seminar, focus group discussion, etc. However, it appears negative impression of the results which is not optimal. In spite of the efforts to build peace, this paper as the research give an idea contribution to peace on the empirical level and informal that was built by micro business in Ambon City. They are known as papalele. Papalele provides essential lessons about peace from economic activity; without religion, etnicity ang race. Despite, their role was not considered various stakeholder at that time and became untold story in peace building in Ambon City, in fact they are true peace bridge.